Preconditions for a successful implementation of supervisors' prompt corrective action: Is there a case for a banking standard in the European Union? - María J. Nieto; Larry D. Wall (Federal Reserve Bank of Atlanta, 2006)
Over the past years, several countries around the world have adopted a system of prudential prompt corrective action (PCA). The European Union countries are being encouraged to adopt PCA by policy analysts who explicitly call for its adoption. To date, most of the discussion on PCA has focused on its overall merits. This paper focuses on the preconditions needed for the adoption of an effective PCA. These preconditions include conceptual elements such as a prudential supervisory focus on minimizing deposit insurance losses and mandating supervisory action as capital declines. These preconditions also include institutional aspects such as greater supervisory independence and authority, more effective resolution mechanisms, and better methods of measuring capital.
Keywords: G28; K23; F20; 330; bank; supervision; European Union; PCA; Bankenaufsicht; Basler Akkord; EU-Staaten